1983
DOI: 10.1007/bf00613829
|View full text |Cite
|
Sign up to set email alerts
|

Doxorubicin and 5-fluorouracil plasma concentrations and detectability in parotid saliva

Abstract: Doxorubicin and 5-fluorouracil pharmacokinetics were studied in 19 volunteers with various advanced neoplastic diseases who received 50-90 mg doxorubicin or 600-1000 mg 5-fluorouracil intravenously, followed by plasma and parotid saliva collection over a 75 min period. The extent to which these chemotherapeutic agents are bound to plasma proteins, at concentrations chosen to approximate plasma concentrations, was measured by equilibrium dialysis. Both agents were quantitated by high-performance liquid chromato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

1989
1989
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 18 publications
0
11
0
1
Order By: Relevance
“…24 Carboplatin and doxorubicin were also tested, with concentrations of 50 and 1mmol/L, respectively, being representative of patient serum levels. 25,26 Previous publications from our laboratory have demonstrated that the loss of cell viability in this assay corresponds to ovarian cancer cell apoptosis. 20,21 Figures 2 and 3 demonstrate that the reduction in cell viability with chemotherapies tested in A2780 and SKOV3 is enhanced when cells were preexposed to metformin for 24 hours.…”
Section: Resultsmentioning
confidence: 93%
“…24 Carboplatin and doxorubicin were also tested, with concentrations of 50 and 1mmol/L, respectively, being representative of patient serum levels. 25,26 Previous publications from our laboratory have demonstrated that the loss of cell viability in this assay corresponds to ovarian cancer cell apoptosis. 20,21 Figures 2 and 3 demonstrate that the reduction in cell viability with chemotherapies tested in A2780 and SKOV3 is enhanced when cells were preexposed to metformin for 24 hours.…”
Section: Resultsmentioning
confidence: 93%
“…Ultrafiltration was previously applied to the serum protein binding of these anthracyclines, binding values in the range of 56.9 -63.1% were obtained [15]. The protein binding results achieved in this study were also equivalent to those previously obtained by equilibrium dialysis [10,13,14]. As anthracyclines are highly protein bound, the volume of bound drug will be reduced.…”
Section: Determination Of Protein Binding Using Ultrafiltrationmentioning
confidence: 81%
“…In another application of equilibrium dialysis, the protein binding of DOX in both human and rat plasma was also determined using HPLC. The extent to which DOX was bound to rat plasma was determined to be 78% [10,13]. In addition, using ultrafiltration in conjunction with HPLC the serum protein binding of DAN, DOX and EPI was determined and the degree of binding was reported to vary in the range of 61 -78.4% [15].…”
Section: Introductionmentioning
confidence: 99%
“…Celio et al [26] and Bressolle et al [27] reported salivary concentrations of DOX, but only Dodde et al [22] presented a validated assay for EPI and EPIol. However, saliva is a promising matrix to predict gastrointestinal side effects (e.g.…”
Section: Introductionmentioning
confidence: 97%